THE PLACE OF NON-STATE TV CHANNELS IN OUR SOCIETY - Perhan Allambergenova (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides analytical views on the current activities of existing non-governmental TV channels in the Republic of Karakalpakstan. We will talk about their directions, achievements and a brief history.